Analisis Pengaruh Indeks Pembangunan Manusia, Tingkat Kemiskinan, Dan Tingkat Pengangguran Terhadap Pertumbuhan Ekonomi Di Kota Sorong Provinsi Papua Barat Daya Tahun 2010-2023 - Anjelly S. P. Way; Ita Pingkan F. Rorong; Krest D Tolosang (PT. Hasba Edukasi Mandiri, 2025)
Economic development aims to improve the quality of life in various aspects, yet economic growth in Sorong City has shown a declining trend in recent years. This study aims to examine the impact of the Human Development Index (HDI), poverty rate, and unemployment rate on economic growth in Sorong City, addressing the research gap as there have been few studies on this topic. A time series data set spanning 10 years (2010-2023) was analyzed using multiple linear regression with SPSS 12. The findings indicate that HDI has a negative effect on economic growth, the unemployment rate has a positive effect, while the poverty rate does not significantly influence economic growth in Sorong City. These findings have important implications for designing more effective policies to promote sustainable economic growth in the region.